Current clinical developments in curcumin‐based therapeutics for cancer and chronic diseases. (8th September 2021) - Kumar, Aviral; Harsha, Choudhary; Parama, Dey; Girisa, Sosmitha; Daimary, Uzini Devi; Mao, Xinliang; Kunnumakkara, Ajaikumar B.
Abstract : The last decade has seen an unprecedented rise in the prevalence of chronic diseases worldwide. Different mono‐targeted approaches have been devised to treat these multigenic diseases, still most of them suffer from limited success due to the off‐target debilitating side effects and their inability to target multiple pathways. Hence a safe, efficacious, and multi‐targeted approach is the need for the hour to circumvent these challenging chronic diseases. Curcumin, a natural compound extracted from the rhizomes of Curcuma longa, has been under intense scrutiny for its wide medicinal and biological properties. Curcumin is known to manifest antibacterial, antiinflammatory, antioxidant, antifungal, antineoplastic, antifungal, and proapoptotic effects. A plethora of literature has already established the immense promise of curcuminoids in the treatment and clinical management of various chronic diseases like cancer, cardiovascular, metabolic, neurological, inflammatory, and infectious diseases. To date, more than 230 clinical trials have opened investigations to understand the pharmacological aspects of curcumin in human systems. Still, further randomized clinical studies in different ethnic populations warrant its transition to a marketed drug. This review summarizes the results from different clinical trials of curcumin‐based therapeutics in the prevention and treatment of various chronic diseases.